STRATEGI KEUNGGULAN BERSAING MELALUI DIGITALISASI LAYANAN PRODUK PADA BANK SYARIAH INDONESIA KCP ROGOJAMPI - Samsuri Samsuri (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2022)
This study aims to determine the competitive advantage strategy through digital product services used by Bank Syariah Indonesia Rogojampi Branch Office, to maintain the competitive advantage of digital product services so that they are not rivaled by other financial institutions. This research is a research with a qualitative descriptive approach. This research was carried out at Bank Syariah Indonesia KCP Rogojampi, the research subjects were Retail Banking Managers, Customer service and Customers who use digitalization products. The data collection method in this study used interviews, while the data analysis methods used were interview, observation and research techniques. The strategy used by Bank Syariah Indonesia in determining competitive advantage is by using various strategies, namely by identifying the company's internal and external factors. In addition, it also develops services for a product through digitization that is more flexible and convenient for customers.